Knowledge, attitude and practice on food higiene among the homemakers in Bukit Aup, Sibu, Sarawak from 8th July 2013 to 20th September 2013 - Muhammad Hafiz, Yaacob; Yap,, Wen Yun; Tiong,, Kung Hu; Tan,, Weng Liang; Tan,, Wai Yang; Lo,, Susan Chen Ling; Surizi, Ismail; Sun,, Jia Miin; Saravanaa, Nalliah; Nurul Afzanizan, Mohamad Anuar Chin; Nurfaezah, Delie; Noorfelda, Abd Jutup; et al. (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Background: Foodborne diseases are a potential threat to the public health. Despite all the Food Act and Regulation, the problem of foodbome diseases is still not uncommon in Malaysia. Objective: The purpose of this study is to determine the level of knowledge, attitude, and practice (KAP) with regards to food hygiene among homemakers of Bukit Aup in Sibu, Sarawak. Methods: This was a cross-sectional study done among 101 homemakers in Bukit Aup, Sibu, Sarawak. A Non-probability sampling method was adopted to select at least one homemaker from each household in the village. An interviewer-guided style of data collection was used. The data was analysed for descriptive data of mean and median, frequencies and standard deviation using SPSS. Results: Among the respondents, the level of good KAP are 53.5%, 39.6% and 58.4% respectively. A significant positive correlation is noted between attitude score and practice score (r=0.203, p<0.05) using Pearson correlation analysis. Out of a total number of 457 villagers, 33 of them (7.2%) had gastrointestinal health complaints in the past six months. There were 36 episodes (7.9%) of abdominal cramp or pain, followed by 18 episodes (3.9%) of diarrhoea and three episodes (0.7%) of vomiting. Conclusion: Generally, it was observed that the respondents had a satisfactory level of knowledge and practices of food hygiene. However some of the respondents had some lapses in their responses to queries on food hygiene attitude.